Laypeople's Collaborative Immersive Virtual Reality Design Discourse in Neighborhood Design - Chowdhury, Shuva; Schnabel, Marc Aurel (Frontiers in Robotics and AI, 2019)
The article discusses design communication and participation of laypeople in a virtual participatory urban design process. We speculate that an immersive virtual environment facilitated instrument can allow laypeople to take part actively as designers in the early stage of urban design ideation and generation. We have developed a design communication framework where laypeople can participate in design discourse on a neighborhood's future urban form. The strategy describes an urban design intent, which is informed by the development procedure of an instrument and workflow to engage participants. The integration of the instrument and the engagement procedure enable continuous designing of urban form by laypeople. A protocol analysis has been undertaken to investigate design communication. A coding scheme is applied to investigate, analyse, and understand how laypeople communicate with the design instrument and control design in the virtual environment. Through engaging non-experts, the research impacts on the perceptual affordance created by immersive 3D buildings artifacts and verbal conversation. The protocol analysis validated the setup so that subsequent studies can address the meaningfulness of such design conversations.